Syringomyelia - Vandertop, W. Peter (Neuropediatrics, 2014)
Syringomyelia is an etiologically diverse affliction caused by disturbance of normal cerebrospinal fluid flow dynamics. An evaluation by comprehensive imaging, using advanced three-dimensional constructive interference in steady state and four-dimensional phase contrast imaging techniques, should be focused on finding the causative lesion because this determines which surgical strategy could be employed. This review discusses the pathogenesis and various etiologies of syringomyelia, and focuses on the specific surgical approach for each, mentioning aspects of surgical complications and prognosis. Particular attention is given to the “persistent central canal,” a normal anatomical variant of the persistent fetal configuration of the central canal, as this is increasingly seen nowadays on routine magnetic resonance imaging.
Keywords: syringomyelia; spinal cord diseases; neural tube defects; malformation; Arnold-Chiari